-symmetric momentum operator and bound states. (21st September 2020) - Izadparast, M; Mazharimousavi, S Habib
Abstract: We develop further the concept of generalized extended momentum operator, which has been proposed very recently in (Izadparast and Mazharimousavi 2020 Phys. Scr. 95, 075220). In particular, we introduce a   -symmetric generalized momentum operator using a complex auxiliary function. The resulting Hamiltonian constructed based on the newly proposed momentum is not Hermitian, however, provided a proper potential it may be pseudo-Hermitian with corresponding real energy eigenvalues. An explicit example is presented to verify the application of the suggested non-Hermitian momentum.